2017
DOI: 10.18176/jiaci.0080
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Reactions to More Than 1 NSAID Must Not Be Considered Cross-Hypersensitivity Unless Tolerance to ASA Is Verified

Abstract: Background: Individuals who develop drug hypersensitivity reactions (DHRs) to chemically unrelated nonsteroidal anti-inflammatory drugs (NSAIDs) are considered cross-hypersensitive. The hallmark for this classification is that the patient presents a reaction after intake of or challenge with acetylsalicylic acid (ASA). Whether patients react to 2 or more NSAIDs while tolerating ASA remains to be studied (selective reactions, SRs). Objective: To identify patients with SRs to 2 or more NSAIDs including strong CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 33 publications
2
23
1
6
Order By: Relevance
“…Despite the high prevalence of hypersensitivity to NSAID and the importance of determining the phenotypes, there is very little literature on this subject to enable comprehensive comparison of our data. A study by Pérez-Alzate et al showed that in some countries cross-hypersensitivity is more common whereas in others selective hypersensitivity dominates (8). In our study, among 559 patients whose diagnosis of hypersensitivity to analgesic was certain, 44.3% patients had anaphylaxis or urticaria after a single analgesic.…”
Section: Discussionsupporting
confidence: 45%
“…Despite the high prevalence of hypersensitivity to NSAID and the importance of determining the phenotypes, there is very little literature on this subject to enable comprehensive comparison of our data. A study by Pérez-Alzate et al showed that in some countries cross-hypersensitivity is more common whereas in others selective hypersensitivity dominates (8). In our study, among 559 patients whose diagnosis of hypersensitivity to analgesic was certain, 44.3% patients had anaphylaxis or urticaria after a single analgesic.…”
Section: Discussionsupporting
confidence: 45%
“…Aspirin was shown to be tolerated in a group of patients with actual immediate-type selective responses to more than one chemically different NSAIDs, and the cross-reactivities were confirmed with either skin tests, basophil activation tests, or OPTs with the culprit. 22,56 This phenotype has not been described in children until now.…”
Section: Epidemi Ology and Clinic Al Manife S Tations In D Ifferentmentioning
confidence: 99%
“…Cross‐reactivities were defined to ibuprofen, dexketoprofen, and/or naproxen in some of the participants, which were referred as selective IgE‐mediated reactions . However in a recent study, it was proven that patients with a history of immediate reaction to more than one chemically different NSAIDs may also show selective responses and cross‐hypersensitivity to culprit NSAIDs since they tolerate ASA . The selective but non‐immediate or “delayed”‐type reactions appear usually 24 hours after the initial NSAID intake, and may be characterized by maculopapular exanthema, by eczema, or by even more severe forms, including fixed drug eruptions, toxic epidermal necrolysis, or organ‐related reactions .…”
Section: Mechanisms Of Nsaid Hypersensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…As with BLs, standardization of DPTs is required concerning number of doses, the optimal dose itself, length, and type of NSAID challenged. Some authors propose a direct DPT with the culprit NSAID [38,39,41], whereas others start with aspirin to exclude cross-intolerance [37,42]. Starting with aspirin is beneficial since it can help distinguish selective and cross responders with one single DPT.…”
mentioning
confidence: 99%